Preparation and physico-chemical characterization of mushroom juice - Kumari, Sweety; Sharma, Sujata Pandit; Chauhan, Dolli; Kumari, Anita; Dayaram, (Journal of Postharvest Technology, 2022)
The development of a novel food product: ‘mushroom juice’ using naturally occurring ingredients has been discussed in this work. The paste of button  mushrooms of equal maturity was boiled with beet root extract, pomegranate juice, stevia and cinnamon powder in a specific formulation for juice  preparation. Physical, chemical and rheological properties of the final strained juice were estimated using standard procedures. The juice had a pH and  total soluble solids (TSS) of 5.03±0.07 and 7±1˚Brix respectively with a bright red colour (L*=87.18±3.00; b*=180.69±1.59; b*>a*). Protein, fat, sodium  and potassium for the prepared juice were estimated as 7.99±0.13%, 0.7±0.1%, 0.002% and 0.067% respectively. The juice was also found  microbiologically safe due to absence of coliform, yeast and mould. Investigation of rheological studies showed that the juice exhibits non-newtonian  behaviour. The product developed in this work is expected to find easy marketability through practical applications in food industries.
Keywords: Button mushroom; mushroom juice; stevia; rheology